Analysis of Genetic Evolution Mechanism and Controlling Factors of Coalbed Methane - Li, Borui (International Journal of Natural Resources and Environmental Studies, 2026)
As an important unconventional natural gas resource, the formation mechanism and genetic type of coalbed methane are of great significance to resource evaluation and development. This paper systematically analyzes the genetic types, formation mechanism and control factors of coalbed methane. Studies have shown that coalbed methane mainly includes two types: biogenic gas and thermogenic gas. Among them, biogenic gas is formed in a low-temperature and shallow-buried environment, while thermogenic gas is formed under higher temperature and pressure conditions. The generation of coalbed methane is not a single process, but a gradual transition from biogenic to thermogenic in the process of coalification, showing obvious continuous evolution characteristics. In addition, the formation and enrichment of coalbed methane are controlled by many factors, such as coal rock composition, coal metamorphic degree, temperature and pressure conditions and hydrodynamic force. The research in this paper is helpful to deepen the understanding of the genetic mechanism of coalbed methane and provide a theoretical basis for the development and utilization of coalbed methane resources.